Can Sri Lanka Stay Ahead of India in the Face of Population Ageing?. Issue 3 (December 2019) - Guest, Ross; Bandaralage, Jay
This paper examines the potential for population ageing in Sri Lanka to allow India to close the gap in the living standards with Sri Lanka over the coming decades. The working-age population in Sri Lanka is currently about 7 per cent higher than in India, but it will be 8 per cent lower by 2050. The reason is that Sri Lanka's demographic transition to lower fertility rates began earlier and has been steeper than in India. Potential demographic dividends from slowing employment growth and changing age distribution of the workforce are likely to further close the gap in living standards between the two countries. The calculations here suggest the gap could be closed by, between 16 and 25 per cent from 2015 to 2050 due to demographic change. In addition, despite its higher share of middle-aged workers, Sri Lanka has in recent times had a lower saving and investment share of GDP than India and a higher consumption share, which will also tend to allow India to close the gap. This paper attempts to quantify these demographic and macroeconomic effects, and considers policy options for Sri Lanka.